1997
DOI: 10.3354/meps159143
|View full text |Cite
|
Sign up to set email alerts
|

Unusual changes of zooplankton fatty acid composition in the northern Adriatic during the 1991 mucilage event

Abstract: Fatty acids and pristane/heptadecane (Pr/C17) ratlo were analysed in zooplankton samples collected with a sediment trap in the northeastern Adriatic Sea from April 1991 to June 1992 in 2 to 6 wk intervals. Saturated (SAT; 22 to 68% of total fatty acid mass fraction), monounsaturated (MONO; 20 to 39"'0), and polyunsaturated (PUFA; 6 to 49%) fatty acid proportions, total fatty acid mass fraction (2.3 to 46.5 mg g-I dry wt), and Pr/CII ratio (0.5 to 27) varied significantly during the investigated period. Unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…PUFAs accounted for half of the fatty acids present, suggesting that together with other planktonic organisms, fungi can be an important source of nutritional lipids for pelagic organisms. In support of this contention, the proportion of PUFAs in marine-derived fungi (this study and Das et al 2007) is within the upper range of values reported for marine phytoplankton (Lewis 1969, Zhukova & Aizdaicher 1995, Arendt et al 2005, zooplankton (Najdek 1997, Escribano & Perez 2010, and bacteria (Russell & Nichols 1999, Das et al 2007.…”
Section: Elemental Composition Of and Organic Compounds In Marine Funsupporting
confidence: 86%
“…PUFAs accounted for half of the fatty acids present, suggesting that together with other planktonic organisms, fungi can be an important source of nutritional lipids for pelagic organisms. In support of this contention, the proportion of PUFAs in marine-derived fungi (this study and Das et al 2007) is within the upper range of values reported for marine phytoplankton (Lewis 1969, Zhukova & Aizdaicher 1995, Arendt et al 2005, zooplankton (Najdek 1997, Escribano & Perez 2010, and bacteria (Russell & Nichols 1999, Das et al 2007.…”
Section: Elemental Composition Of and Organic Compounds In Marine Funsupporting
confidence: 86%
“…On the other hand, correlative evidence linking zooplankton production to dietary PUFAs does suggest an important role for these compounds in nutrition. There may be instances in which food is unusually deficient in fatty acids, such as the presence of large quantities of mucilaginous aggregates (Najdek 1997) or detritus (Coombs et al 1994). Data sets for grazers and their food that incorporate fatty acids and bulk elements such as C, N, and P in comparable units are few and far between.…”
mentioning
confidence: 99%